2015
DOI: 10.1371/journal.pone.0125572
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospital Readmission after Radical Gastrectomy for Gastric Cancer: A Prospective Study

Abstract: BackgroundHospital readmission is gathering increasing attention as a measure of health care quality and a potential cost-saving target. The purpose of this prospective study was to determine risk factors for readmission within 30 days of discharge after gastrectomy for patients with gastric cancer.MethodsWe conducted a prospective study of patients undergoing radical gastrectomy for gastric cancer from October 2013 to November 2014 in our institution. The incidence, cause and risk factors for 30-day readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 29 publications
(53 reference statements)
4
29
1
3
Order By: Relevance
“…Patient demographics in terms of age, gender and BMI have not been found to affect readmission rates in most of the previous studies. [6][7][8][9][10][11][12][13][14][15][16][17] Among various biochemical parameters, hypoproteinemia was found to be a significant risk factor for readmission in the present study. Though this parameter has not been considered in majority of the studies, some authors have found it to be significant.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Patient demographics in terms of age, gender and BMI have not been found to affect readmission rates in most of the previous studies. [6][7][8][9][10][11][12][13][14][15][16][17] Among various biochemical parameters, hypoproteinemia was found to be a significant risk factor for readmission in the present study. Though this parameter has not been considered in majority of the studies, some authors have found it to be significant.…”
Section: Discussionsupporting
confidence: 48%
“…Though this parameter has not been considered in majority of the studies, some authors have found it to be significant. 11,18 This is probably due to the fact that hypoproteinemia predisposes patients to increased risk of infections because of poor immunity. Moreover, hypoproteinemia leads to poor wound healing thus causing increased risk of anastomotic leak as well as wound dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional and registry data suggest an overall morbidity of approximately 20% and increased risk of readmissions among patients who developed complications (7, 10, 14, 15). The individual effects associated with specific and potentially modifiable risk factors remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have focused more on disease-specific populations and reported factors associated with readmission among patients with pancreatic, liver, cholangiocarcinoma, as well as gastric cancer. 2330 Data on readmission following surgery for ACC remains not defined. Information on ACC may be particularly interesting as readmission might be affected by patient presentation (e.g., age, comorbidities, etc.…”
Section: Introductionmentioning
confidence: 99%